MITOCHONDRIAL PROTEIN PROFILE AND ITS ROLE IN PATHOLOGIC PROCESSES - Ye. A. Kosterina; I. I. Kozenkov; V. A. Kasymov; P. A. Kamensky; I. N. Dominova; Yu. A. Korolyova; V. Ye. Patrusheva; R. S. Bogachev; L. S. Litvinova; S. V. Babak; Ye. M. Moiseeva; Ye. A. Bogdanov; et al. (Бюллетень сибирской медицины)
Mitochondria import hundreds of different precursor proteins from the cytosol, and only 13 proteins are encoded by mtDNA itself. Recent investigations demonstrated real size of mitochondrial proteome and complexity of their functions There are many methods using for mitochondrial proteome profiling, that help to understand a molecular mechanisms of mitochondrial functions and identify the causes of disruptions that lead to different disorders. In this review we discuss a recent data in the field of mitochondrial proteomics.